FURTHER STUDIES ON CHANGES IN PROTEIN FRACTION OF FISH MUSCLE DURING STORAGE IN ICE. - DEVADASAN, K; NAIR, M RAJENDRANATHAN (Fishery Technology, 2017)
The changes in the major protein nitrogen fractions of twocommercially important fishes of Indian waters, viz., mackerel(Rastrelliger k.anagurta) and lactarius (Lactarius lactarius), duringstorage in ice are reported. The significance of the findings1s discussed in comparison with the results of a similarstudy on two species of marine prawns and oil sardine, reportedearlier.